2007
DOI: 10.1016/j.ijsolstr.2006.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical solution for a elastic pipe bend at in-plane bending with consideration for the end effect

Abstract: The authors proposed an analytical method for the analysis of the end effect in a pipe bend loaded by a bending moment with consideration for the action of internal pressure. The method is based on the use of simplifying hypotheses and is reduced to the solution of a system of fourth-order differential equations along the axial coordinate with respect to unknown coefficients in the expansion for tangential displacements. An approximate analytical solution, which has a trapezoidal structure and is written in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…At the moment the calculating problem of pipe elbows has produced many works. For example, in [4,5] there are analytical solutions for curves pipes. Materials [6,7] are devoted to solution curves of pipes using the finite element method.…”
Section: � �� �4�mentioning
confidence: 99%
“…At the moment the calculating problem of pipe elbows has produced many works. For example, in [4,5] there are analytical solutions for curves pipes. Materials [6,7] are devoted to solution curves of pipes using the finite element method.…”
Section: � �� �4�mentioning
confidence: 99%
“…Expressions (17) and (19) for Y f and ΔY are substituted, in view of decompositions (32), into (30) and then into (31): The expression for N x may be written in a simpler form, which follows from (33a):…”
Section: Idea Of Solution Of the Problemmentioning
confidence: 99%
“…If the bend is insufficiently long, then the influence of edge effects manifests itself even in the middle of it [30]. If the bend is very long, then not only the computation time, but also the errors that depend exponentially on the bend length increase [31].…”
mentioning
confidence: 99%
“…As in a static problem, we will consider bends of a sufficient length L b , in order to avoid manifesting the edge effects (in the statics, this requirement has the form: L R R t b > η , where η is some coefficient [6]). …”
Section: Introductionmentioning
confidence: 99%
“…The practice of calculation of a toroidal shell under static loading, including that with account of the end effect [4][5][6], has shown that for shell components it is possible to apply the following simplifying hypotheses of the Vlasov semi-momentless theory:…”
Section: Introductionmentioning
confidence: 99%